The World Book of America’s presidents (World Book, 2001)
This two-volume set from the publisher of the World Book Encyclopedia offers fascinating facts about the power and prestige of the presidency of the United States. Profiles begin with George Washington and include more than 440 pages filled with absorbing facts and amusing anecdotes.